دراسة تحليلية للمداخلة المعمارية على قصر العظم بدمشق في فترة الانتداب الفرنسي عام 1936 - الأحمر, جمال; الصفدي, سبأ فاروق (Latakia University Journal -Engineering Sciences Series, 2019)
شهدت العديد من مدن العالم ولا تزال تشهد مداخلاتٍ معمارية حديثة على مبانيها التاريخية, ويقصد بهذه المداخلات كل عملية تعديل أو إضافة أو إزالة معمارية تجري على هذه المباني التاريخية سواءً أكانت داخلية أم خارجية. وإن هذه المداخلات لم تستثن مدينة دمشق التاريخية، التي هي مهد الحضارات، والمشهورة بغناها بالمباني التاريخية, ومنها قصر العظم الذي يعد أحد أهم هذه المباني, وقد ضم في فترة الانتداب الفرنسي المعهد الفرنسي لدراسات الشرق, حيث كلف المهندس المعماري الفرنسي ميشيل إيكوشار، الذي قدم إلى دمشق بعد إنهاء دراسته بوقتٍ غير طويل في فترة الثلاثينات؛ بدراسة سكن لمدير المعهد الفرنسي للدراسات العربية، بحيث يتم إنشاؤه ضمن إحدى ساحات القصر, وذلك إثر أعمال الترميم التي كان قد كلف بها بعد الحريق الناتج عن قصف منطقة سيدي عامود عام 1925, فقام ببناء هذه الكتلة وفق طراز عمارة الحداثة الذي كان سائداً في ذلك الوقت. لذلك فقد كان من الضروري تحليل هذه الكتلة بشكلٍ معمق ودراستها، وذلك لإجراء مقارنة معمارية تاريخية لها، ومحاولة الإجابة عن بعض التساؤلات المطروحة حول مدى انسجامها مع بناء قصر العظم، وإمكانية قبولها في الفترة التي تم بناؤها فيها, ومدى أهمية الحفاظ عليها في الوقت الحاضر, وذلك بالاستناد إلى المواثيق الدولية للحفاظ على التراث المعماري. Several cities around the world have been witnessing new architectural interventions on their historical buildings, which include every architectural process of change, addition to or removal of these buildings, whether affecting interior or exterior parts. These interventions didn't exclude the old city of Damascus which is known as the lap of the cultures and many historical buildings. One of the most important buildings is AL-Azem palace. It contained the French institute of the Orient studies during the French legation, when Michel Ecochard who came to Damascus shortly after finishing his study in the 1930s was commissioned to design a residence for the head of the institute in one of the yards of the palace. Within the process of restoration assigned to him after the fire caused by the shelling of the area of Sidy Amood in 1925, he constructed the new building after the modern style which prevailed at that time. For this reason it was important to analyze and study this building in-depth in a way to make a historical and architectural comparison for it and to respond to some questions about its harmony with the structure of AL-Azem palace in the period of its construction and the possibility of accepting it in the period in which it was constructed, and the importance of preserving it in the meantime on the base of the international charters for conservation of the architectural heritage.